2020
DOI: 10.3390/ijms21186598
|View full text |Cite
|
Sign up to set email alerts
|

STIM1 Deficiency Leads to Specific Down-Regulation of ITPR3 in SH-SY5Y Cells

Abstract: STIM1 is an endoplasmic reticulum (ER) protein that modulates the activity of a number of Ca2+ transport systems. By direct physical interaction with ORAI1, a plasma membrane Ca2+ channel, STIM1 activates the ICRAC current, whereas the binding with the voltage-operated Ca2+ channel CaV1.2 inhibits the current through this latter channel. In this way, STIM1 is a key regulator of Ca2+ signaling in excitable and non-excitable cells, and altered STIM1 levels have been reported to underlie several pathologies, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…In 2020, Pascual-Caro et al ( 2020) found a remarkable reduction of ITPR3 following the knock-out of STIM1 gene, which caused the mitochondrial function abnormality. This further confirmed the potential role of STIM1-ITPR3 axis in the pathogenesis of AD (Pascual-Caro et al, 2020). Similarly, Knupp et al (2020) found that the depletion of SORLA in hiPSCs by using CRISPR/Cas9 can cause early endosome enlargement in hiPSCs-derived neurons rather than hiPSC microglia, and inhibition of BACE is not able to rescue the endosome enlargement phenotype in hiPSC neurons, indicating the independent function of SORLA in AD pathogenesis.…”
Section: Screening Of Pathogenic Genes For Sporadic Alzheimer's Diseasementioning
confidence: 66%
“…In 2020, Pascual-Caro et al ( 2020) found a remarkable reduction of ITPR3 following the knock-out of STIM1 gene, which caused the mitochondrial function abnormality. This further confirmed the potential role of STIM1-ITPR3 axis in the pathogenesis of AD (Pascual-Caro et al, 2020). Similarly, Knupp et al (2020) found that the depletion of SORLA in hiPSCs by using CRISPR/Cas9 can cause early endosome enlargement in hiPSCs-derived neurons rather than hiPSC microglia, and inhibition of BACE is not able to rescue the endosome enlargement phenotype in hiPSC neurons, indicating the independent function of SORLA in AD pathogenesis.…”
Section: Screening Of Pathogenic Genes For Sporadic Alzheimer's Diseasementioning
confidence: 66%
“…This includes regulation of ER refilling through mGluR1 and 5 [155,156] and of synaptic plasticity [157], as well as Ca 2+ overload through upregulation of L-type VGCCs and mitochondrial dysfunction [152]. A recent work has demonstrated that STIM1-deficient SH-SY5Y cells display reduced expression of the IP 3 receptors type 3 (IP 3 R3) that is, in turn, responsible for the low mitochondrial Ca 2+ concentration ([Ca 2+ ]) and for the reduced efficiency of this organelle [158], which are common features in AD patients [159].…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…However, in some mammalian cells, IP 3 Rs have been shown to co-localize with Orai1 (Lur et al, 2011 ) and interact with STIM1, Orai1, and TRPCs (Hong et al, 2011 ). The expression of IP 3 R isoform (IP 3 R 3 ) was shown to be significantly lower in STIM1-deficient SH-SY5Y cells, meaning that STIM1 is a positive regulator of ITPR3 gene expression in these cells (Pascual-Caro et al, 2020 ). IP 3 R 3 is a Ca 2+ channel that is localized mainly at the ER-mitochondrion junction, which transfers Ca 2+ from the ER to mitochondria (Ivanova et al, 2014 ).…”
Section: Stim Interacting Proteinsmentioning
confidence: 99%
“…Thus, STIM1 deficiency leads to a decrease in mitochondrial Ca 2+ concentrations, leading to cell death. The overexpression of IP 3 R 3 restores mitochondrial Ca 2+ homeostasis and bioenergetics, ATP production, and cell survival in STIM1-KO neuronal-like cells (Pascual-Caro et al, 2020 ). These results provide evidence of a novel STIM1-IP 3 R 3 -mediated pathway of mitochondrial Ca 2+ levels, the dysregulation of which contributes to neurodegeneration.…”
Section: Stim Interacting Proteinsmentioning
confidence: 99%
See 1 more Smart Citation